The crisis of representation in translating bilingual texts: a social semiotic perspective. - Lee, Tong-King (Perspectives: Studies in Translatology, 2011)
This article adopts a social semiotic approach to the study of the function of code-switching in bilingual literary texts and the problems associated with the translation of such texts. Based on an analysis of a Singaporean Chinese short story and its English translation, the article hypothesises that in cases when a source text introduces a foreign language in order to expose a power relationship, this central argument of the source text will often be lost if the text is translated into the embedded foreign language. It first argues that such translation will lead to a homogenisation of traces of bilingualism in the source text, thus reversing the indexical relations between the two language codes in question. It is then proposed that from the discoursal perspective, the attitudinal meaning of the bilingual text may be negated in translation, thus leading to a paradoxical situation whereby a language representing the 'Other' in the source text is being used against itself in the target text. The article also suggests that this translational problem, rather than being an obstacle, can become an asset to the teaching of intercultural communication.